Profiling of Phenolic Compounds in Citrus Flowers and Their Biological Activities - Sepidar Seyyedi-Mansour; Maria Carpena; Pauline Donn; Paula Garcia-Oliveira; Javier Echave; Paula Barciela; Maria Fraga-Corral; Lucia Cassani; Jesus Simal-Gandara; Miguel A. Prieto (Engineering Proceedings, 2023)
Citrus, a genus of flowering plants in the Rutaceae family, holds substantial market importance as a crop worldwide. After prolonged periods of breeding and extensive hybridization, numerous species have emerged, each possessing a unique metabolism that produces a diverse array of secondary metabolites. It is important to note that phenolic compounds, in particular phenols and flavonoids, are among the most important secondary metabolites in Citrus flowers. These chemical compositions of Citrus flowers differ depending on various factors, such as variety, fruit maturity, environmental conditions, storage conditions, and extraction methods. Nevertheless, phenolic compounds extracted from Citrus flowers are well-recognized for their bioavailability characteristics and exhibit numerous health-promoting effects, including antioxidant, anti-inflammatory, anti-cancer, and antibacterial activities in humans. The information contained in this document provides a comprehensive summary of the latest investigations conducted on the subject matter. The aim is to thoroughly comprehend the biological functions of the bioactive compounds in the Citrus flowers and their potential impacts on various biological systems, shedding light on their potential therapeutic applications.